Pengaruh Kompensasi, Motivasi Kerja Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada CV Robot Vape Inc. Tasikmalaya - Agin Ahmad Muhaemin; Barin Barlian; Dudu Risana (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The research aims to first understand and analyze the overview of Compensation, Work Motivation, Work Discipline, and Employee Work Productivity at CV Robot Vape Inc Tasikmalaya. Second, to determine and analyze the simultaneous influence of Compensation, Work Motivation, and Work Discipline on employee work productivity at CV Robot Vape Inc Tasikmalaya. Third, to determine and analyze the partial influence of Compensation on employee work productivity at CV Robot Vape Inc Tasikmalaya. Fourth, to determine and analyze the partial influence of Work Motivation on employee work productivity at CV Robot Vape Inc Tasikmalaya. Fifth, to determine and analyze the partial influence of Work Discipline on employee work productivity at CV Robot Vape Inc Tasikmalaya. The method used in this research is quantitative with a survey approach. The research results indicate that Compensation falls under the good category, Work Motivation falls under the good category, Work Discipline falls under the very good category, and work productivity of employees at CV Robot Vape Inc Tasikmalaya falls under the good category. There is a significant simultaneous influence of Compensation, Work Motivation, and Work Discipline on work productivity of employees at CV Robot Vape Inc Tasikmalaya. There is a significant partial influence of Compensation on work productivity of employees at CV Robot Vape Inc Tasikmalaya. There is a significant partial influence of Work Motivation on work productivity of employees at CV Robot Vape Inc Tasikmalaya. There is a significant partial influence of Work Discipline on work productivity of employees at CV Robot Vape Inc Tasikmalaya.